Consumers' Purchasing Behaviour Towards Men’s Grooming Products (International Journal of Food and Nutritional Sciences, 2022)
As a result, the most intriguing purchasing behaviour in the Indian market is for skincare items. The competitive climate and evolving industry are greatly increasing consumer demand and retailer power. For manufacturers to survive and succeed, a long-term relationship with their customers is essential. Customers hold the secret to any company organization's success. The success of an organisation depends on its understanding of its customers' needs, wants, and purchasing habits. Consumers' purchasing behaviour becomes a crucial factor in how they assess and access a particular product. In order to forecast future trends, marketing professionals are continually analysing the patterns of consumer behaviour and purchasing choices. Consumer buying behaviour is the study of how, when, where, and why consumers make purchases of goods. The decision-making process and physical activity people engage in while deciding whether to evaluate, purchase, use, or dispose of products and services is known as consumer buying behaviour.